Quail, Land Use, and Weather in Illinois, 1956-70 - William R. Edwards (National Quail Symposium Proceedings, 2017)
Bobwhite quail (Colinus virginianus) populations were at a 15-year high in 1968 and 1969 in Illinois. Analysis indicated that quail abundance over the years from 1956 through 1970 was significantly correlated with changes in land use and weather. Adverse effects associated with increased acreages of row crops and reduced acreages of oats appeared to be offset by aspects of land use, favorable to quail, that were associated with reduced acreages of harvested hay. Quail also appeared to be adversely affected by heavy snow, above-normal rainfall in late winter and spring, heavy summer rains, and drought in summer and fall.